Geographic and socioeconomic variation in treatment of elderly prostate cancer patients in Norway - a national register-based study - Elin Marthinussen Gustavsen; Erik Skaaheim Haug; Ellinor Haukland; Ragnhild Heimdal; Eva Stensland; Tor Åge Myklebust; Beate Hauglann (Springer, 2024)
Abstract Purpose The aim of this study was to examine geographic and socioeconomic variation in curative treatment and choice of treatment modality among elderly prostate cancer (PCa) patients. Methods This register-based cohort study included all Norwegian men ≥ 70 years when diagnosed with non-metastatic, high-risk PCa in 2011-2020 (n = 10 807). Individual data were obtained from the Cancer Registry of Norway, the Norwegian Prostate Cancer Registry, and Statistics Norway. Multilevel logistic regression analysis was used to model variation across hospital referral areas (HRAs), incorporating clinical, demographic and socioeconomic factors. Results Overall, 5186 (48%) patients received curative treatment (radical prostatectomy (RP) (n = 1560) or radiotherapy (n = 3626)). Geographic variation was found for both curative treatment (odds ratio 0.39-2.19) and choice of treatment modality (odds ratio 0.10-2.45). Odds of curative treatment increased with increasing income and education, and decreased for patients living alone, and with increasing age and frailty. Patients with higher income had higher odds of receiving RP compared to radiotherapy. Conclusions This study showed geographic and socioeconomic variation in treatment of elderly patients with non-metastatic, high-risk PCa, both in relation to overall curative treatment and choice of treatment modality. Further research is needed to explore clinical practices, the shared decision process and how socioeconomic factors influence the treatment of elderly patients with high-risk PCa.